(untitled) (Journal of the College of Basic Education, 2024)
The study aimed to prepare an educational curriculum according to the Gilbert model (the backward chain) for learning some basic skills in table tennis. The researcher assumed that the educational curriculum prepared by the researcher would have a positive effect on learning some basic skills in table tennis. The researcher used the experimental approach to achieve the objectives of the study and solve the research problem. The research population was determined by an intentional method. As for the sample, it was chosen randomly using a lottery and was represented by middle school students (second intermediate grade) from Saqr Quraish Middle School students, numbering (98) students, divided into three sections. By lottery, two sections were selected, each section being an experimental and a control sample. The researcher concluded that: The educational curriculum has a positive impact on learning table tennis skills, and the researcher recommended the necessity of utilizing the educational curriculum according to the Gilbert model for learning skills in general and table tennis skills in particular.